Pengembangan Materi Ajar Buku Saku Pada Keterampilan Menulis Puisi Berbasis Lingkungan Dan Budaya Lokal Sumatera Utara Di Kelas X - Samosir, Karnila Novita; Hanum, Inayah (Faidatuna, 2023)
This study aims to determine the process of developing and feasibility of pocket book teaching materials on poetry writing skills based on the environment and local culture developed for class X students of SMA N 17 Medan. The subjects in this study were validators and students and the object of this study was a pocket book entitled "Writing Poetry Based on North Sumatra's Environment and Culture". The research method used is the research and development (R&D) method with the Borg and Gall model. Based on the results of the analysis, it was found that the validation data for the development of pocket book materials was very feasible to use. After calculating the feasibility percentage of the pocket book, the range is 81% - 100% with very feasible criteria. So it is concluded that the material developed in the form of a pocket book is very suitable to be used as a book to support students in the learning process.